OECD anti-spam toolkit of recommended policies and measures (Organisation for Economic Co-operation and Development, 2006)
This toolkit, developed by policy makers and industry experts, provides a framework aimed at tackling spam using a broad, multi-disciplinary range of instruments including regulation and enforcement, industry initiatives, technical measures, education and awareness initiatives, cooperative partnerships, spam metrics, and global cooperation.--Publisher summary.